The epidemiology of stroke in Northern Sri Lanka: A population-based descriptive cross-sectional study - Kumaran, S.; Shribavan, K.; Powsiga, U.; Sheron, V.A.; Jency Vinuja, H.M.; Arasalingam, A. (University of Jaffna, 2024)
Introduction: Stroke is a significant health concern in Sri Lanka, leading to high rates of mortality and morbidity. Healthcare must prioritize prevention and early detection to address this issue. While research on stroke treatment in Sri Lanka is limited, local studies highlight changing trends and risk factors. This study aimed to assess the prevalence of stroke and its risk factors in the Northern Province of Sri Lanka. Methodology: This population-based cross-sectional study conducted by the NIHR Global Health Research Group on Atrial Fibrillation focused on individuals aged 50 and above in the Northern Province. Using a multi-stage sampling approach, the study recruited a sample size of 10,000 Tamil-speaking participants representing all five northern districts. Data were collected with an interviewer-administered questionnaire. Descriptive statistics was used to determine the prevalence and describe the common risk factors. Results: Out of 10,000 individuals, 231 had a stroke, resulting in a 2.3% prevalence rate. Among the 231 patients with stroke, mean age was 68.6 (SD 8.6) years, with 54.1% and 45.9% being males and females, respectively. Educational status varied, with most having primary education or less (40.2%). Retirees comprised 47.6% of the group. Common risk factors included hypertension (71.0%), diabetes mellitus (34.6%) and palpitations (30.7%). Conclusion: Our study revealed a higher stroke prevalence rate (2.3%) in the Northern Province compared to the national rate (1.0%). Patients with stroke had a high prevalence of risk factors such as hypertension, diabetes and heart diseases. These insights highlight the need for tailored primary prevention and management strategies, considering socio-economic factors and specific regional risks, particularly screening programs and rehabilitation services.
Keywords: Stroke; Sri Lanka; Elders; Risk factors; Northern Province